Tantangan dan Hambatan Program Asistensi Mengajar Tingkat SMP oleh Mahasiswa Pendidikan Seni Rupa - Adani, Mohammad Rifky; Anggriani, Swastika Dhesti (Mahesa Research Center, 2025)
The Teaching Assistant Program allows students to develop and practice teaching skills in educational institutions. However, its implementation presents challenges and obstacles that are not well-defined. This study aims to identify the challenges and obstacles students face in the program. The subjects of this study are Art Education students in the Junior High School program in Malang Raya. This research uses a qualitative method with a descriptive approach. The findings show that at each stage of the teaching assistant program, there are issues that create challenges and obstacles for the students. Problems identified in the preparation phase include activities such as socialization, briefing, program preparation on campus, and individual student factors. Challenges and obstacles include the lack of specific training for Art Education students and Field Supervisors (DPL). In the implementation phase, issues arise in areas such as deployment, observation, program planning and implementation, teaching and non-teaching activities, interest conflicts, and personal problems of students. A key challenge is the lack of commitment from some team members. In the reporting phase, challenges include short deadlines for preparing and submitting reports.